SRS143 a semi-synthetic analogue of andrographolide against house dust mite induced allergic asthma - Tan, Chee Yi; Oshiogwe, Okwuofu Emmanuel; Saud, Anoosha; Ng, Hui Suan; Sagineedu, Sreenivasa Rao; Stanslas, Johnson; Lim, Jonathan Chee Woei (Springer Science and Business Media Deutschland GmbH, 2025)
Allergic asthma is one of the common forms of asthma. Upon exposure to allergens, mast cells actively release histamine into the airway, forcing the smooth muscles in the airway to undergo contraction, hence asthmatic attack. The therapeutics of asthma is commonly based on the use of steroids and topical bronchodilators. Steroid-resistant asthma has been on the rise and can be further exacerbated by any respiratory infection. Treatment requires a high dose of steroids to produce efficacy and persistent use of high-dose steroids will result in debilitating side effects. There is a need for better and safer alternatives with a different therapeutic mechanism than steroids to complement existing therapies. Andrographolide (AGP) and its analogues have been shown to display potent anti-inflammation effects in many various asthma models. Despite having potent anti-asthma activity, AGP and analogues did not display any anti-histamine activity against histamine release assay. Surprisingly SRS143, an AGP analogue displayed improved potency in both in vitro and in vivo allergic models. Inhibition of histamine release by antigen-activated mast cells was observed without causing any toxicity. Similar observations were also seen in our in vivo model whereby asthmatic BALB/c female mice were induced by sensitising and challenging them with house-dust mite (HDM). Animals administered with SRS143 intraperitoneally had shown potent inhibition on asthmatic responses. SRS143 treated asthmatic mice displayed significant reduction of pulmonary eosinophilia, airway hyper-responsiveness, and mucus hypersecretion. This potent analogue warrants a potential treatment for allergic asthma.